Iron oxide nanoparticles for biomedical applications: A perspective on synthesis, drugs, antimicrobial activity, and toxicity - Arias, Laís Salomão [UNESP]; Pessan, Juliano Pelim [UNESP]; Vieira, Ana Paula Miranda [UNESP]; De Lima, Taynara Maria Toito; Delbem, Alberto Carlos Botazzo [UNESP]; Monteiro, Douglas Roberto (MDPI, 2018)
Medical applications and biotechnological advances, including magnetic resonance imaging, cell separation and detection, tissue repair, magnetic hyperthermia and drug delivery, have strongly benefited from employing iron oxide nanoparticles (IONPs) due to their remarkable properties, such as superparamagnetism, size and possibility of receiving a biocompatible coating. Ongoing research efforts focus on reducing drug concentration, toxicity, and other side effects, while increasing efficacy of IONPs-based treatments. This review highlights the methods of synthesis and presents the most recent reports in the literature regarding advances in drug delivery using IONPs-based systems, as well as their antimicrobial activity against different microorganisms. Furthermore, the toxicity of IONPs alone and constituting nanosystems is also addressed.
Keywords: Biotechnology; Drug delivery; Iron oxide nanoparticles; Magnetic nanoparticles